Exploring the Role of Microglial Cells in the Gut–Brain Axis Communication: A Systematic Review - Ortiz-Samur, Nadia Suyin; Vijaya, Akshay Kumar; Burokas, Aurelijus; Mela, Virginia (WILEY, 2025)
The gut–brain axis (GBA) is a bidirectional communication system between the gastrointestinal tract and the CNS, playing a key role in neurological function, immune response, and metabolism. Microglia, the resident immune cells in the brain, are crucial regulators of neuroinflammation and synaptic plasticity. Recent studies indicate that gut microbiota modulates microglial activity via metabolic and immune pathways, with implications for neurodegenerative, neurodevelopmental, and psychiatric disorders. However, mechanisms underlying microbiota–microglia interactions remain unclear. Following a systematic screening of 4481 studies, 20 preclinical studies met inclusion criteria and were reviewed to assess microbiota–microglia interactions. These studies were identified via PubMed, Science Direct, and Google Scholar. Findings synthesize results from 20 selected studies examining the impact of gut microbiota on microglial function. Experimental models, including fecal microbiota transplantation, dietary interventions, and bacterial supplementation, were analyzed. Microglial activity was assessed via immunohistochemistry, gene expression profiling, and functional assays. Most studies suggest that gut dysbiosis promotes microglial overactivation and neuroinflammation via microbial-derived short-chain fatty acids (SCFAs), bile acids, and neuroimmune signaling cascades such as TLR4/NF-κB and NLRP3 inflammasomes, whereas microbiota-targeted interventions reduce inflammation and support cognitive function. Despite promising findings, inconsistencies in study methodologies and microbiota analyses limit comparability and clinical translation. This review synthesizes studies linking gut microbiota alterations to microglial states, neuroinflammatory signatures, and cognitive outcomes across experimental models, highlighting the therapeutic potential of microbiota-based strategies to modulate microglial function and mitigate neuroinflammatory diseases.
Keywords: Intestinos -- Microbiología; Microglía; Neurología; Sistema nervioso -- Enfermedades; Sistema nervioso -- Degeneración; Acidos grasos; Cerebro -- Investigación; Cognitive function; Gut microbiota; Gut–brain axis; Microglia; Neurodegeneration; Neuroinflammation; Hort- chain fatty acids